Noise Induced Hearing Loss among Factory Workers of Dharan Industrial Area - Paudel, D; Bhandary, S; Pokharel, A; Chettri, ST; Shah, SP; Sah, BP; Manandhar, S (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Hearing loss is the most common sensory loss accounting for 250 million population of world out of which 16% is attributed from occupational exposure to loud noise, ranging from 7% to 21% in different parts of the world. The prevalence of noise induced hearing loss is more common among factory workers than general population. There are limited reports regarding occupational noise from developing country like Nepal. Method: A cross sectional study was done in Dharan Industrial Area between February 2014 to May 2014. Twenty different industries operating inside the premises of industrial area were categorized into four major categories as per the nature and types, such as: Metal, Plastic, Food and Chemical based industries. Measurement of the sound was done in two phases. Pure tone audiometry of the exposed and non-exposed population was done. Results: Total 104 workers were included from 20 different factories; out of them 80 workers were exposed to loud noise and 24 were non-exposed who acted as the control. The frequency of hearing loss among exposed population was 38.8% and it was 12.5% among non-exposed and the difference was statistically significant. In exposed population hearing loss was 7.7%, 40.5% and 60.9% in age groups of 15- 30, 31- 45 and > 46 years respectively and the difference was statistically significant. Population working longer duration had more chance of noise induced hearing loss and the difference was significant. Conclusion: Population working in noise producing factory has high risk of developing noise induced hearing loss and the risk increases in older people and in people who works for long duration.